2011
DOI: 10.1016/j.jpsychires.2011.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Life stress and first onset of psychiatric disorders in daughters of depressed mothers

Abstract: This study used a comprehensive, interview-based measure of life stress to assess the role of different types of stress in predicting first onset of psychiatric disorders among daughters of depressed (n = 22) mothers and healthy (n = 22) mothers. Several types of stress were assessed: Chronic interpersonal stress, chronic non-interpersonal stress, episodic dependent (i.e., self-generated) interpersonal stress, episodic dependent non-interpersonal stress, episodic independent interpersonal stress, and episodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 38 publications
6
42
0
Order By: Relevance
“…Researches have shown consistently that children of depressed mothers are at elevated risk for developing a range of psychiatric disorders, as depression [70][71][72]. This risk persists beyond the duration of a given maternal depressive episode and can continue into adulthood [70,73].…”
Section: Family and Hereditary Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Researches have shown consistently that children of depressed mothers are at elevated risk for developing a range of psychiatric disorders, as depression [70][71][72]. This risk persists beyond the duration of a given maternal depressive episode and can continue into adulthood [70,73].…”
Section: Family and Hereditary Factorsmentioning
confidence: 99%
“…This risk persists beyond the duration of a given maternal depressive episode and can continue into adulthood [70,73]. Daughters may be especially vulnerable; investigators have found that daughters of depressed mothers are more likely to develop Psychopathology than are son [70,74,75].…”
Section: Family and Hereditary Factorsmentioning
confidence: 99%
See 3 more Smart Citations